SPE Western Regional Meeting 2021
DOI: 10.2118/200804-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Zeta Potentiometric Study on Effects of Ionic Composition and Rock-Saturation on Surface-Charge Interactions in Low-Salinity Water Flooding for Carbonate Formation

Abstract: As carbonate reservoirs are mostly oil-wet, the potential for the success of a waterflooding is lower. Therefore, a primary focus during waterflooding such reservoirs is on the ionic composition and salinity of injected brine which are able to impact the alteration of the rock wettability favorably by altering the surface charge towards a higher negative value or close to zero. The objective of this study is to employ zeta potentiometric studies comprising streaming potential and streaming current techniques t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…By the addition of calcium and magnesium ions to the smart brine, a more positive value of zeta potential is observed whereas by addition of sulfate and phosphate ion to the smart brine, a more negative value of zeta potential is observed. A detailed analysis of results has been done by Gopani et al where it is reported that in order to separate adhered oil molecules from the rock surface, the zeta potential should be made either more negative or near zero [13]. A near zero value of zeta potential suggests a decrease in attractive forces keeping oil adhered to the rock surface and a more negative zeta potential suggests an increase in forces of repulsion between negatively charged oil and rock surface.…”
Section: Smart/modified Brinesmentioning
confidence: 99%
See 1 more Smart Citation
“…By the addition of calcium and magnesium ions to the smart brine, a more positive value of zeta potential is observed whereas by addition of sulfate and phosphate ion to the smart brine, a more negative value of zeta potential is observed. A detailed analysis of results has been done by Gopani et al where it is reported that in order to separate adhered oil molecules from the rock surface, the zeta potential should be made either more negative or near zero [13]. A near zero value of zeta potential suggests a decrease in attractive forces keeping oil adhered to the rock surface and a more negative zeta potential suggests an increase in forces of repulsion between negatively charged oil and rock surface.…”
Section: Smart/modified Brinesmentioning
confidence: 99%
“…Al-Hashim et al found that favorable wettability state i.e., water-wetness can be achieved by addition of SO 4 2− and Mg 2+ ions in diluted seawater from carbonate rocks [12]. The increasing concentration of divalent anions such as sulfate and phosphate causes the zeta potential to become more negative while divalent cations results in polarity reversal at the rock surface [13].…”
Section: Introductionmentioning
confidence: 99%
“…These may be due to differences in the rock minerals used or sample preparations. Gopani et al 8 report the change in the surface charge of carbonate rock samples due to a change in the composition of ions (Ca 2+ , Mg 2+ , and SO 2– ) in brine and their ionic strength. These studies highlight the controlling role the rock mineral constituents play in molecule adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…These may be due to differences in the rock minerals used or sample preparations. Gopani et al 8 Recently, we studied the effect of pH, salt type and concentration on clays, 7 iron minerals 25 and another reservoir constituent minerals 3 surface charge. In these studies, zeta potential measurements were used to infer conditions and well operations that provide surface conditions that would promote asphaltene adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation